A new species of the genus Echinorhinus (Chondrichthyes, Echinorhiniformes) from the upper cretaceous of southern South America (Argentina-Chile). (October 2017) - Bogan, Sergio; Agnolin, Federico L.; Otero, Rodrigo A.; Egli, Federico Brissón; Suárez, Mario E.; Soto-Acuña, Sergio; Novas, Fernando E.
Abstract: We describe isolated shark teeth collected from levels of the Calafate Formation at the SE coast of the Argentino Lake, Calafate city, Santa Cruz province, Argentina (Atlantic Ocean), and from the Algarrobo coast at the Valparaíso Region in central Chile (Pacific Ocean). The teeth belong to a new species of the echinorhiniform genus Echinorhinus . Echinorhinus maremagnum n. sp. was a taxon distributed in both the southwestern Atlantic and the southeastern Pacific. This new taxon constitutes the oldest record of echinorhiniforms from South America and one of the few Mesozoic records at a worldwide scale.